Effectiveness of Pyridoxine and Pyridostigmine in the Treatment of Vincristine-Induced Bilateral Ptosis and External Ophthalmoplegia: A Case Report - Osman Okan Olcaysu; Ahmet Altun; Elif Olcaysu; Sertaç Argun Kıvanç; Zuhal Keskin Yıldırım (Türk Oftalmoloji Dergisi, 2014)
In this manuscript, we present the case of a patient with acute lymphoblastic leukemia who developed vincristine-induced bilateral ptosis and external ophthalmoplegia and who was treated successfully with pyridoxine and pyridostigmine. Pyridostigmine and pyridoxine are promising treatment option in cases of vincristine-induced neuropathy. (Turk J Ophthalmol 2014; 44: 330-1)